2013
DOI: 10.1037/a0034244
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative evolutionary theory of adaptive behavior dynamics.

Abstract: The idea that behavior is selected by its consequences in a process analogous to organic evolution has been discussed for over 100 years. A recently proposed theory instantiates this idea by means of a genetic algorithm that operates on a population of potential behaviors. Behaviors in the population are represented by numbers in decimal integer (phenotypic) and binary bit string (genotypic) forms. One behavior from the population is emitted at random each time tick, after which a new population of potential b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 107 publications
(208 reference statements)
2
53
0
1
Order By: Relevance
“…Plots in McDowell et al (2008) (also in McDowell, 2013b) showed in a striking way that even at very small time scales, the cumulative changes in and reversals of preference exhibited by the artificial organisms were indistinguishable from those exhibited by Davison and Baum's birds. These are just two examples of successful first-stage predictions of the evolutionary theory. In a recent review, McDowell (2013b) found that the theory generated results that were qualitatively and quantitatively consistent with a large body of existing data from experiments with live organisms.…”
Section: First-stage Predictions Of the Theorysupporting
confidence: 64%
See 2 more Smart Citations
“…Plots in McDowell et al (2008) (also in McDowell, 2013b) showed in a striking way that even at very small time scales, the cumulative changes in and reversals of preference exhibited by the artificial organisms were indistinguishable from those exhibited by Davison and Baum's birds. These are just two examples of successful first-stage predictions of the evolutionary theory. In a recent review, McDowell (2013b) found that the theory generated results that were qualitatively and quantitatively consistent with a large body of existing data from experiments with live organisms.…”
Section: First-stage Predictions Of the Theorysupporting
confidence: 64%
“…Behaviors in these classes corresponded to responses on two alternatives in an experimental chamber. The Hamming distance (McDowell, 2013b;Popa and McDowell, 2010) that naturally exists at the boundary of these classes acted as a changeover delay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Algorithm 1 (see the supplementary material of McDowell, ) samples parents based on their fitness values. In Algorithm 1, a father is selected by sampling a trial fitness value from the fitness function (line 5) and searching through the ordered population for a behavior with the sampled fitness (line 6).…”
Section: Mcdowell's Evolutionary Theory Of Behavior Dynamicsmentioning
confidence: 99%
“…These processes of variation and selection cause the population of potential behaviors to evolve under the selection pressure of consequences from the environment. A more detailed description of the theory's algorithmic operation is given in McDowell (). The theory was first applied to single variable‐interval (VI) schedules by McDowell (), and to concurrent VI VI schedules by McDowell, Caron, Kulubekova, and Berg ().…”
mentioning
confidence: 99%